Cocaine - Padam Hirachan MD, FASN, FACP (Journal of Investigative Medicine High Impact Case Reports, 2015)
Cocaine abuse is commonly associated with myocardial ischemia, mesenteric ischemia, and cerebrovascular accidents. Renal infarction is an uncommon complication of cocaine abuse. Various mechanisms have been postulated for this cocaine-related injury. There are only 15 cases reported on cocaine-induced renal infarction. Among the cases with available data, very few cases had left kidney involvement. We report a case of a 65-year-old African American man with history of cocaine abuse who presented with left flank pain and had left renal infarction.